2016
DOI: 10.1007/978-3-319-29887-0_16
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Position of the External Carotid Artery: A Rare Variation to Be Recognized During Carotid Endarterectomy

Abstract: Lateral position of the ECA is not extremely rare in patients undergoing CEA for atherosclerosis and may be a congenital variation, although this is still controversial. CEA can be performed safely if the arteries from the CCA to the ICA are rotated, and the ICA is moved to the shallow surgical field under wider longitudinal exposure. Although no postoperative cerebral infarcts were detected, the risk of artery-to-artery embolism resulting from artery repositioning prior to plaque removal should be taken into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…Failure to detect these vascular anomalies preoperatively increases the risk of peri-and postoperative complications. [5] Here, we focused on the so-called twisted internal carotid artery (ICA), which runs medially to the external carotid artery (ECA). [3,4,7,10] is anomaly was also called "side-by-side carotid artery, " "dorsal/dorsomedial origin of the ICA, " or "lateral ECA. "…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Failure to detect these vascular anomalies preoperatively increases the risk of peri-and postoperative complications. [5] Here, we focused on the so-called twisted internal carotid artery (ICA), which runs medially to the external carotid artery (ECA). [3,4,7,10] is anomaly was also called "side-by-side carotid artery, " "dorsal/dorsomedial origin of the ICA, " or "lateral ECA. "…”
Section: Introductionmentioning
confidence: 99%
“…[3,4,7,10] is anomaly was also called "side-by-side carotid artery, " "dorsal/dorsomedial origin of the ICA, " or "lateral ECA. " [5,[12][13][14][15][16]20] Although several series and/or cases have been reported, we clarified the frequency and other clinical features of the twisted ICAs among our CEA-treated cases and…”
Section: Introductionmentioning
confidence: 99%
“…7,8) The frequency of TCB among our patients was 11.3% and it was significantly more prevalent on the right side. Angiography findings have shown that the incidence of TCB or LPECA in various diseases is 4.3%-4.9% in Japanese populations 10,12) and 3.6%-15.1% during CEA. [5][6][7][8]10,14,15) Therefore, this abnormality is actually quite prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…However, the ICA sometimes runs medically to the ECA, which has been described as side-by-side carotid artery, 3) dorsal/dorsomedial origin of the ICA, 4) complete transposition of the carotid bifurcation (CB), 5) twisted carotid bifurcation (TCB), [6][7][8] lateral ECA, and lateral position of the ECA (LPECA). [9][10][11][12] Most recent reports of patients with TCB who have undergone CEA have focused on surgical techniques, and few describe diagnosing a TCB. 8,10) The present study aimed to determine the diagnostic features of a TCB and its surgical management and outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation